The Development of Monopoly Physics Science Media (MOFIN) on Simple Harmonic Motion at MA Al-Falah Tolutu - Rahman, Abd; Yunginger, Raghel; Payu, Citron S.; Abdjul, Tirtawaty; Jahja, Mohamad; Setiawan, Dewa Gede Eka (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This research aims to determine the design and feasibility of the MOFIN learning media. This research model employs the 4D method (Define, Design, Development, and Dissemination). Data collection techniques include interviews (initial stage), observations, and tests (experimental stage). The validity of the MOFIN learning media design obtained an average scale of 3.43 from the validators, with the "Valid" criteria indicating that it can be used with some revisions. The results of the experimental testing (practicality) of the MOFIN learning media revealed that the implementation of the learning process was "Very Good," with a percentage of 93%. The response from the students showed the highest percentage in the aspect of "Character Education," with a percentage of 91% or received a "Very Good" response. The effectiveness of the media was assessed through the students' activities, which showed an average percentage of 94%. After conducting the learning assessment test, the students obtained an average score of 86.25, with the lowest score being 77, indicating that they have reached the Minimum Completeness Criteria (KKM) set by MA Al-Falah Tolutu